Social capital and collective identity in the local food movement*. Issue 2 (2nd April 2016) - Bauermeister, Mark Richard
Abstract : Social movement actors are seeking alternatives to the highly industrialized, global food system through alternative agri-food initiatives to counter the conventional practices of the industrial food system. Many of these initiatives have proven successful. Social movement researchers have documented the importance of the roles and services social movement organizations provide for movement constituents to realize their success, emphasizing human and financial capital as key components for mobilizing collective action. Researchers have also documented the value of interorganizational networks, and the benefits of collaboration to expand the share of resources, and perhaps more importantly design social movement frames to direct collective action for social change. However, what local food movement research has yet to address are some of the potential barriers that minimize collaboration among organizational leaders as it relates to social capital and collective identity. This paper takes a cross-sectional network analysis of social movement organizations working to increase the sustainability of various areas within the local food system in Marin County, California, a historically agricultural region serving a number of urban communities. Findings from the mixed-methods research reveal evidence of collective identity and social capital as enhancing collaboration among particular types of organizations while reducing potential collaboration among and between other social movement organizations. By analysing the collective identity and dichotomous nature of social capital among social movement organizations, this research contributes a clearer understanding of the existing gaps for increasing the sustainability of a local food system.